Estimation of sublimation enthalpies of aromatic compounds as a function of temperature. (November 2022) - Yagofarov, Mikhail I.; Balakhontsev, Ilya S.; Miroshnichenko, Evgeniy A.; Solomonov, Boris N.
Highlights: Approach for estimation of sublimation enthalpy as function of temperature was proposed. Sublimation enthalpy is calculated as a sum of vaporization and fusion enthalpies. Temperature dependence of fusion enthalpy is found using solution calorimetry. Temperature dependence of vaporization enthalpy is estimated from molecular structure. Validity was tested against literature sublimation enthalpies and heat capacity data. Abstract: Reconciliation of the sublimation enthalpies, on the one hand, and the enthalpies of fusion and vaporization, on the other, is often performed during critical analysis in phase transition thermochemistry. The temperature dependence of these quantities should be considered during the reconciliation since each is measured under different conditions. Experimental determination of the temperature dependence of phase transition enthalpies is known to be a laborious procedure, so indirect predictive approaches are valuable. In this work, an approach for the determination of the sublimation enthalpy as a function of temperature from the enthalpies of solution at 298.15 K, fusion at the melting point ( T m ), and the molecular structure was developed and applied to 38 aromatic compounds. The consistency of the calculated values with the experimental sublimation enthalpies and the heat capacities of the crystal and ideal gas was confirmed. The performance of the Chickos et al. scheme, widely used for temperature adjustment phase transition enthalpies was checked. Its reliability in the 100–150 K temperature range for sublimation enthalpy adjustments was also confirmed. Limitations arising at a wider range are discussed.